Determining subject-specific parameter values using an angle-driven simulation model - Wilson, C.; Yeadon, M.; King, M. (International Journal of Computer Science in Sport, 2002)
Parameter values are required for computer simulation models of human movement. This paper describes a procedure for determining personalised parameter values for elastic elements using kinematically driven simulations to match performances of running jumps. These parameters may then be used in kinetically driven models.